A case of teriflunomide-induced hepatic injury: assessing causality using available rules. Issue 1 (1st January 2020) - LeSaint, Kathy T.; Waksman, Javier; Smollin, Craig G.
Abstract: Teriflunomide, a pyrimidine synthesis inhibitor approved for treatment for the relapsing form of multiple sclerosis, has been deemed reasonably safe though hepatic toxicity is a rare serious adverse event. We report an uncommon case of a 48-year-old man who developed severe hepatotoxicity within a short time after initiation of teriflunomide treatment with resolution of signs and symptoms after drug discontinuation and concomitant treatment with cholestyramine. In this case, we provide a general framework regarding the assignment of causation in potential causes of drug-induced liver injury. The patient met the case definition of Hy's law and his hepatotoxicity was assessed as causally related to teriflunomide using the Roussel Uclaf Causality Assessment Method (RUCAM).